Misdiagnosis of Appendicitis in Women in a Resource Limited Setting: Lessons from South Africa - Kariem, Nazmie (Division of General Surgery, 2024)
Introduction: Acute appendicitis (AA) is a common surgical emergency. In low and middleincome countries, the diagnosis is often made clinically due to the lack of access to specialised imaging. Misdiagnosis in females is common, given the potential broad differential diagnosis. The rate of misdiagnosis varies between countries, but there is a paucity of data in the developing world. The aim and objectives of this study were to describe the routine workup of females with suspected AA at a South African government hospital and to determine factors associated with the misdiagnosis of AA. Methods: A retrospective review of all females older than 12 years operated on by general surgeons with a suspected diagnosis of AA over a 2-year period was reviewed. Data including age, gender, presenting complaints and physical findings, laboratory and radiological results, pre and post-operative diagnoses were extracted and analysed using descriptive and inferential statistics. Results: A total of 180 females were included and 48 (26.7%) of them were misdiagnosed with AA. Of these 48 that were misdiagnosed, 22 (46%) had pelvic inflammatory disease (PID), 15 (31%) had a normal appendix, 10 (21%) had ovarian cysts and (2%) had endometriosis. Gynaecologic bimanual examination was performed in 123 (68.3%) patients. Twelve (6.7%) patients had a CT scan and 16 (8.9%) had an abdominal ultrasound. In the multivariate model, the absence of nausea, vomiting and anorexia (odds ratio (OR)=2.43; p=0.023), the presence of cervical excitation tenderness (CET) (OR: 4.32; p=0.009) and adnexal tenderness (OR=3.06; p=0.021) were significantly associated with a diagnosis other than appendicitis. These factors remained significant in the multivariate model after adjusting for relevant covariates. Conclusion: More than 25 % of females referred to general surgeons with suspected AA were misdiagnosed. Since imaging is not accessible at most resource-limited settings, it is imperative to conduct a gynaecologic examination on every female since adnexal and cervical tenderness were associated with PID and not AA.